Exploring the Acceptability of an Environmental Education Program for Youth in Rural Areas: ECOCIDADANIA Project - Isabel S. Silva; Filipa Cunha-Saraiva; Ana Sofia Ribeiro; Ana Bártolo (MDPI AG, 2023)
Background: There has been a growing interest in environmental education programs to improve environmental awareness and behavior change among school-aged youth. Yet, assessment of the approaches aligned with citizen science principles emphasizing community participation and empowerment is scarce. The present study aimed to explore the acceptability of the "ECOCIDADANIA" environmental education program targeted at youth in rural areas. Methods: The program was applied for two years in the municipality of Gouveia, and it involved nature walks methodologies combined with citizen science. A total of 107 students participated in the program. Eighteen participants (13 youth and 5 teachers) were selected as key informants, and semistructured interviews were conducted to assess the appropriateness of the intervention and the perceived benefits. Results: The program was demonstrated to be acceptable to youth and teachers, and its benefits included increasing students' knowledge, skills and self-efficacy, discovering the territory, promoting environmental awareness, strengthening social relationships between peers and educators, and contributing to the promotion of individual and collective well-being. All the participants were satisfied with the program's activities and recommend its continuation in the school context. Conclusions: Programs of this nature could foster environmental activism and enhance environmental sustainability at the local level, which reinforces the entrepreneurship profile of the youth.